Ethnopharmacological insights into tropical medicinal plants: biodiversity, bioactive compounds, and therapeutic potential for modern drug discovery - Mohammed, Umar Aminu; Abdullahi, Kamal; Zigau, Zainab Auwal; Mukhtar, Amina; Mustapha, Aisha (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2026)
Recent scholarly debates on equitable bioprospecting, intensified since the 2010 Nagoya Protocol, have exposed a critical gap in linking tropical plant biodiversity to validated pharmacological outcomes, particularly where habitat degradation accelerates species loss. Hitherto, ethnobotanical knowledge from the Amazon, Congo, and Southeast Asian basins regions dominated by Asteraceae, Rubiaceae, and Fabaceae has informed drug leads, yet systematic validation lags. This review, adhering to PRISMA-ScR standards, screened a lot of peer-reviewed records (2015–2026) via dual-independent extraction, yielding several studies on plant species with medicinal properties. Indigenous applications, such as Artemisia annua against malaria or Momordica charantia for glycemic control, find partial backing from in vitro assays and select rodent models. Alkaloids like quinine (Cinchona spp.), terpenoids including artemisinin, alongside flavonoids and phenolics, disrupt cancer proliferation, thwart microbial resistance, and mitigate neurodegeneration, evidence drawn from cytotoxicity screens, antimicrobial MICs, and sparse phase I trials. Paradoxically, synergies among co-occurring metabolites enhance efficacy, even as dose-dependent toxicities undermine safety profiles. These patterns challenge reductionist models of single-compound pharmacology, refining instead polyvalent synergy theories contingent upon extraction fidelity. Notwithstanding ethical frictions in benefit-sharing and intellectual property disputes, sustainability threats from anthropogenic deforestation loom large. Bridging ethnobotanical assertions to mechanistic proof demands interdisciplinary conservation pharmacology. Urgent action secures these reservoirs for novel agents.